Parental dalam Pendidikan Islam: Studi Pola Asuh Orang Tua, dan Materi Pembelajaran Perspektif Pendidikan Islam terhadap anak dalam Kandungan Masa Prenatal - Ferdian Utama; Eka Prasetiawati (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Early childhood education started prenatal phase or in the womb, which based on the research behind it is still a lot of older people who did not understand about the start of education towards early childhood, especially in the world of Islamic education. Many scientific studies such as the biological sciences, medicine, and developmental psychology that discusses parenting children against in the womb. Islam actually any review about child development that starts from the process of creating it, upbringing in the womb, to parenting in the family. But the fact that many people still do not know. This research used the qualitative research methodology, sampling done to families and pregnant mother on neighborhood institution ma'arif Metro City of Lampung. The formulation of the problem is, how parenting parents, learning materials and educational perspective of islam against the child in the content of prenatal period. The results of this study explain about parenting and the material provided on Islamic education perspective turned out to give the development and growth of the child in the womb to the prenatal phase. As for parenting and the material provided by prayer, morality and morals, listens to chanting the qur'an, pattern language, creed and Shari'ah.